2018
DOI: 10.1002/cmdc.201700749
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the BCL2 Gene Promoter G‐Quadruplex with a New Class of Furopyridazinone‐Based Molecules

Abstract: Targeting of G-quadruplex-forming DNA in the BCL2 gene promoter to inhibit the expression of anti-apoptotic Bcl-2 protein is an attractive approach to cancer treatment. So far, efforts made in the discovery of molecules that are able to target the BCL2 G-quadruplex have succeeded mainly in the identification of ligands with poor drug-like properties. Here, a small series of furo[2,3-d]pyridazin-4(5H)-one derivatives were evaluated as a new class of drug-like G-quadruplex-targeting compounds. Biophysical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 28 publications
(44 reference statements)
0
34
0
Order By: Relevance
“…Human breast adenocarcinoma (MCF-7) cell line (ATCC) was grown in DMEM supplemented with 10% FBS, 2.5 mM glutamine, 100 U/mL penicillin, and 100 µg/mL streptomycin (Euroclone). Normal human dermal fibroblasts (HDF), kindly provided by Dr. Annalisa Tito (Arterra Bioscience), were grown in DMEM supplemented with 10% FBS, 1% glutamine, 100 U/mL penicillin, and 100 µg/mL streptomycin [ 71 ]. Cells were maintained in humidified air containing 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Human breast adenocarcinoma (MCF-7) cell line (ATCC) was grown in DMEM supplemented with 10% FBS, 2.5 mM glutamine, 100 U/mL penicillin, and 100 µg/mL streptomycin (Euroclone). Normal human dermal fibroblasts (HDF), kindly provided by Dr. Annalisa Tito (Arterra Bioscience), were grown in DMEM supplemented with 10% FBS, 1% glutamine, 100 U/mL penicillin, and 100 µg/mL streptomycin [ 71 ]. Cells were maintained in humidified air containing 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, this ligand showed cytotoxicity against cancer cell lines overexpressing c-MYC but not against normal cells, suggesting reduced side effects based on G4 selectivity on c-MYC [39]. Other ligands, like Furo[2,3-d]pyridazin-4(5H)-one 9 (BLC2) [40], Indolo[3,2-c]quinolines (IQc) (KRAS) [41], and SYUIQ-FM05 (VEGF) [42], has also been reported. Those findings shed a light on the developing of the next-generation G4s ligands, which have high antitumor activity and bioactivity with minimal side effects.…”
Section: Targeting G-quadruplex Structures Of Htertmentioning
confidence: 99%
“…[1,7,8] Moreover,t he enrichment of theses tructures in promoter regions of, in particular, proto-oncogenesh as been revealed by informaticsa nalysiso ft he human genome [9] and supported by antibody-based G4 chromatin immunoprecipitation and highthroughput sequencing. [15,16,17] The 1,3-di(1H-1,2,3-triazol-4-yl)benzene system was previously shown by biophysical and molecular modeling studies to provide an efficient central module, able to interact effectively with the 3'-end G-quartet of the human telomeric parallel-stranded G4 structure. [1,3] Strikingly,i th as been shown that G4stabilizing ligands might differentially target humanc ancer stem cells, [11,12] as ubpopulation of cancer cells implied in tumorf ormation, metastases, and recurrence due to their long-lasting properties and resistance to chemotherapy.…”
mentioning
confidence: 99%
“…The design of flexible nonfused polycyclic G4-interactive smallm olecules that may also target grooves and loops of G4s has emerged as one way to achieve selectivity and also to lead to more drug-like compounds. [15,16,17] The 1,3-di(1H-1,2,3-triazol-4-yl)benzene system was previously shown by biophysical and molecular modeling studies to provide an efficient central module, able to interact effectively with the 3'-end G-quartet of the human telomeric parallel-stranded G4 structure. [18,19] Also, quinolines have been shownt ob ei mportant modules in the design of several potent G4 ligands.…”
mentioning
confidence: 99%